2018
DOI: 10.1029/2018ja025530
|View full text |Cite
|
Sign up to set email alerts
|

Excitation of Plasma Irregularities in the F Region of the Ionosphere by Powerful HF Radio Waves of X‐Polarization

Abstract: We discuss theoretically the excitation of artificial plasma irregularities in the auroral ionosphere by high-frequency X-mode radio wave. This is done via a two-step process. As a first step we adopt the thermal self-focusing instability excited in the F region of the ionosphere under the action of a strong high-frequency (HF) radio wave. This instability causes the formation of perturbations of the electron temperature and plasma concentration across the magnetic field. In addition, the plasma becomes deplet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In the second step large-scale filaments collapse into the small-scale sizes. An attempt at a theoretical justification of the two-step generation of the X-mode FAIs was made by Borisov et al (2018).…”
Section: Journal Of Geophysical Research: Space Physicsmentioning
confidence: 99%
“…In the second step large-scale filaments collapse into the small-scale sizes. An attempt at a theoretical justification of the two-step generation of the X-mode FAIs was made by Borisov et al (2018).…”
Section: Journal Of Geophysical Research: Space Physicsmentioning
confidence: 99%
“…Field-aligned irregularities have been observed during X-mode heating experiments at Tromsø, Norway (Blagoveshchenskaya et al, 2011(Blagoveshchenskaya et al, , 2014(Blagoveshchenskaya et al, , 2015. Borisov et al (2018) suggested using a two-step process to interpret the formation of 10m FAIs by the X-mode heating wave at high latitudes. The first step is the thermal self-focusing instability, and the second step is the formation of electron inhomogeneities resulting from the thermal self-focusing instability or from the gradient drift and current convective instabilities.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the physical driving mechanisms of artifi cial fi eld-aligned irregularities with a spatial scale across the geomagnetic fi eld of 7.5 m to 15 m were signifi cantly diff erent for O-mode and X-mode HF pumping, presenting challenges for understanding the relevant processes. In contrast to the O-mode artifi cial fi eld-aligned irregularities, excited by a thermal parametric (resonance) instability at the upper hybrid resonance altitude [13,14], the X-mode artifi cial fi eld-aligned irregularities were generated via a two-step process [31,[36][37][38]. In the fi rst step, the generation of elongated large-scale irregularities (with a spatial scale across the geomagnetic fi eld of the order of 1 km to 10 km) due to the self-focusing instability occurred.…”
Section: Small-scale Artifi Cial Field-aligned Irregularities (Afais)mentioning
confidence: 99%
“…The excitation and behavior of small-scale artifi cial fi eld-aligned irregularities was driven by largescale irregularities. Their possible generation mechanisms could be the temperature-gradient-drift instability [38] or the fi lamentation instability [39].…”
Section: Small-scale Artifi Cial Field-aligned Irregularities (Afais)mentioning
confidence: 99%